Exploring the role of moderation in shaping the subjective experience of Genshin Impact players in the Indonesian Facebook group - Matthew Edbert Hermanto; Muhammad Aras (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2025)
This research examines the subjective experiences of Genshin Impact players in Indonesia, focusing on interactions within Facebook groups. It explores how group dynamics and moderation influence toxic behavior. By interviewing moderators from two Facebook groups, the study compares toxic behavior and moderation strategies, revealing that active, effective moderation reduces toxicity, while less oversight leads to increased negativity. The findings highlighted the crucial role of community management in shaping player interactions and online group culture. Beyond presenting practical implications for moderators and community managers, the study also contributed conceptually to understanding the relationship between moderation practices and online social behavior. It suggested that future research should involve broader and more diverse player groups to validate and expand these insights.